Tubeimoside-1 induces TFEB-dependent lysosomal degradation of PD-L1 and promotes antitumor immunity by targeting mTOR - Xiaojia Liu; Mingxiao Yin; Jingwen Dong; Genxiang Mao; Wenjian Min; Zean Kuang; Peng Yang; Lu Liu; Na Zhang; Hongbin Deng (Elsevier, 2021)
Programmed cell death ligand 1 (PD-L1)/programmed cell death protein 1 (PD-1) cascade is an effective therapeutic target for immune checkpoint blockade (ICB) therapy. Targeting PD-L1/PD-1 axis by small-molecule drug is an attractive approach to enhance antitumor immunity. Using flow cytometry-based assay, we identify tubeimoside-1 (TBM-1) as a promising antitumor immune modulator that negatively regulates PD-L1 level. TBM-1 disrupts PD-1/PD-L1 interaction and enhances the cytotoxicity of T cells toward cancer cells through decreasing the abundance of PD-L1. Furthermore, TBM-1 exerts its antitumor effect in mice bearing Lewis lung carcinoma (LLC) and B16 melanoma tumor xenograft via activating tumor-infiltrating T-cell immunity. Mechanistically, TBM-1 triggers PD-L1 lysosomal degradation in a TFEB-dependent, autophagy-independent pathway. TBM-1 selectively binds to the mammalian target of rapamycin (mTOR) kinase and suppresses the activation of mTORC1, leading to the nuclear translocation of TFEB and lysosome biogenesis. Moreover, the combination of TBM-1 and anti-CTLA-4 effectively enhances antitumor T-cell immunity and reduces immunosuppressive infiltration of myeloid-derived suppressor cells (MDSCs) and regulatory T (Treg) cells. Our findings reveal a previously unrecognized antitumor mechanism of TBM-1 and represent an alternative ICB therapeutic strategy to enhance the efficacy of cancer immunotherapy.